Case Report: Anesthesia for Cesarean Section in Parturients With Chronic Renal Failure Requiring Hemodialysis: Case Reports and Literature Review - Zhang, Ting; Xiong, Xianwei; Jiang, Yiling; Chen, Huan; Jin, Juying (Frontiers in Surgery, 2022)
Pregnancies are rare in women with chronic renal failure requiring hemodialysis. Although a chance of successful pregnancy and delivery in hemodialysis women has increased over the years, it is still very low, and with high maternal and fetal mortality and morbidity rate compared to normal population. And cesarean section is usually used for delivery. Two 32-year-old Chinese women with chronic kidney disease stage V undergoing maintenance hemodialysis for six years were scheduled for cesarean delivery. To help develop reasonable anesthetic methods and management objectives for such patients, we described our anesthetic management and performed a literature search on published cases of cesarean section with chronic renal failure undergoing hemodialysis.